Gamification for Elementary Mathematics Learning in Indonesia - Yogi Udjaja; Vincent Sadino Guizot; Natalia Chandra (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The purpose of this research is to combine multimedia elements and mathematics learning material to a mathematic learning interactive application. Research and design methodology that used is Game Development Life Cycle (GDLC) which consist of initiation, pre-production, production, testing and release. Content inside the game is made using gamification and expert system concept. The result of this research is an interactive learning game to support student to understand mathematic materials. The purpose of this application is to help student to learn mathematic in an interactive and interesting way, to deliver mathematic material easily.